COVID‐19 in the workplace: Self‐reported source of exposure and availability of personal protective equipment by industry and occupation in Michigan. Issue 12 (24th September 2022) - Laskaris, Zoey; Hirschtick, Jana L.; Xie, Yanmei; McKane, Patricia; Fleischer, Nancy L.
Abstract: Objectives: Fragmented industry and occupation surveillance data throughout the COVID‐19 pandemic has left public health practitioners and organizations with an insufficient understanding of high‐risk worker groups and the role of work in SARS‐CoV‐2 transmission. Methods: We drew sequential probability samples of noninstitutionalized adults (18+) in the Michigan Disease Surveillance System with COVID‐19 onset before November 16, 2020 ( N = 237, 468). Among the 6000 selected, 1839 completed a survey between June 23, 2020, and April 23, 2021. We compared in‐person work status, source of self‐reported SARS‐CoV‐2 exposure, and availability of adequate personal protective equipment (PPE) by industry and occupation using weighted descriptive statistics and Rao‐Scott χ 2 tests. We identified industries with a disproportionate share of COVID‐19 infections by comparing our sample with the total share of employment by industry in Michigan using 2020 data from the US Bureau of Labor Statistics. Results: Employed respondents ( n = 1244) were predominantly female (53.1%), aged 44 and under (54.4%), and non‐Hispanic White (64.0%). 30.4% of all employed respondents reported work as the source of their SARS‐CoV‐2 exposure and 78.8% were in‐person workers. Work‐related exposure was prevalent in Nursing and Residential Care Facilities (65.2%); Justice, Public Order, and Safety Activities (63.3%); and Food Manufacturing (57.5%). By occupation, work‐related exposure was highest among Protective Services (57.9%), Healthcare Support (56.5%), and Healthcare Practitioners (51.9%). Food Manufacturing; Nursing and Residential Care; and Justice, Public Order, and Safety Activities were most likely to report having adequate PPE "never" or "rarely" (36.4%, 27.9%, and 26.7%, respectively). Conclusions: Workplaces were a key source of self‐reported SARS‐CoV‐2 exposure among employed Michigan residents during the first year of the pandemic. To prevent transmission, there is an urgent need in public health surveillance for the collection of industry and occupation data of people infected with COVID‐19, as well as for future airborne infectious diseases for which we have little understanding of risk factors.